BEYOND DIRECT EFFECTS: HOW MANAGEMENT ACCOUNTING INFORMATION SYSTEMS AND DIFFERENTIATION STRATEGIES ENHANCE MICRO-ENTERPRISE PERFORMANCE - Wuryaningsih, wuryaningsih; Yudhiyati, Ratna (Proceedings of the International Conference of Islamic Economics and Business (ICONIES); Vol 11 No 1 (2025): The 11th International Conference of Islamic Economics and Business (ICONIES 2025), 2025)
This study aims to examine the mediating effect of differentiation as a competitive advantage of micro-entreprises on the relationship between management accounting information systems and performance. This is a quantitative study, with data collected using a self-administered survey. The respondents were owners and managers of micro-enterprises in Malang City. The sample consisted of 129 respondents, and the data were subsequently processed using the Structural Equation Model - Partial Least Squares (SEM-PLS) method. The results of this study show that management accounting information systems have a significant effect on the performance of micro-enterprises. Furthermore, the study also indicates that differentiation partially mediates the relationship between management accounting information systems and micro-enterprise performance. The findings imply that MAIS has not only a direct effect but also an indirect effect through the differentiation variable. In addition, this research suggests that to optimize micro-enterprise performance, it is necessary to consider the integrative adoption of both management accounting information systems and differentiation strategies. Practically, the results of this study demonstrate the importance of micro-entreprises to encourage the use of MAIS and foster a data-driven decision-making culture to maximize the potential of differentiation, which will ultimately improve their business performance in a competitive market.